Slag phosphogypsum-based solid waste cementing material as well as preparation method and application thereof
By using raw materials such as slag, phosphogypsum, calcium carbide slag and silica fume in solid waste gelling materials, combined with the synergistic effects of alkali excitation and sulfate excitation, the problem of insufficient compressive strength of existing solid waste gelling materials has been solved, and efficient and low-cost material performance improvement has been achieved.
Patent Information
- Application Number
- CN202510387822.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The compressive strength of existing solid waste gelling materials is insufficient and cannot meet the actual engineering needs. At the same time, the use of ingredients such as cement and quicklime increases production costs.
Slag and phosphogypsum are used as the main raw materials, combined with calcium carbide slag as an alkaline exciter and silica fume, and the hydration products and microstructure of the material are optimized through the synergistic effects of alkali excitation, sulfate excitation, volcanic ash reaction and microaggregate filling.
The compressive strength of slag phosphogypsum-based solid waste gelling material has been significantly improved, and the compressive strength can reach up to 57.7MPa in 28d, reducing production costs and reducing carbon emissions and energy consumption.
Smart Images

Figure CN119874223A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a slag phosphogypsum-based solid waste cementitious material and a preparation method and application thereof. Background Art
[0002] Solid waste cementitious materials have become the focus of the industry in recent years due to their advantages of low resource consumption and low production energy consumption. Their raw materials mainly include blast furnace slag, fly ash, metakaolin and red mud. Solid waste cementitious materials have attracted widespread attention due to their abundant raw material sources, high strength, low production cost, green environmental protection, good corrosion resistance, good fire resistance, good durability, and ability to fix toxic heavy metal ions. Through the synergistic hydration of different solid wastes, cementitious materials with equivalent performance to traditional cement can be prepared. It can not only consume a large amount of stockpiled solid waste, but also reduce carbon dioxide emissions and energy consumption. It is considered to be the most promising green cementitious material.
[0003] The patent with publication number CN113149477A proposes a full solid waste cementitious material and its preparation method and application. The full solid waste cementitious material includes 22.5%-27.5% phosphogypsum, 22.5%-27.5% carbide slag, and 45%-55% slag powder by mass percentage. Although the patent realizes the utilization of solid waste, the prepared cementitious material has a maximum compressive strength of 2.645MPa at 3d, 3.621MPa at 7d, and 4.96MPa at 28d after curing. The strength still cannot meet the actual needs; the patent with publication number CN113149477A proposes a composite industrial solid waste cementitious material and its preparation method and application. The raw materials are 30-40 parts of lithium slag, 10-15 parts of blast furnace slag, 15-20 parts of steel slag powder, 5-10 parts of silica fume, 5-10 parts of phosphogypsum, 5-10 parts of silicate cement clinker, and 5-10 parts of quicklime. Although the raw materials involve industrial solid waste, cement, quicklime and other ingredients are also used, which undoubtedly increases the production cost, and its compressive strength is also low, which cannot meet the actual production needs.
[0004] To this end, the present invention proposes a novel slag phosphogypsum-based solid waste cementitious material and a preparation method and application thereof. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a novel slag phosphogypsum-based solid waste cementitious material and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A slag phosphogypsum-based solid waste cementitious material, wherein the raw materials include 45-55% slag, 40-50% phosphogypsum, 0.5-5% carbide slag and 2-10% silica fume in terms of mass percentage, and the water-cement ratio is 0.35-0.50.
[0009] Furthermore, the slag is S95 grade or above. Slag is divided into three grades according to the activity index: S75, S95 and S105. S95 grade slag is a kind of high-activity slag powder that meets the requirements of the national standard GB / T18046-2000. It is mainly processed by water-quenched blast furnace slag through drying, grinding and other processes. The activity index of S95 grade slag powder requires a 28d compressive strength ratio of ≥95% and a specific surface area of ≥350m 2 / kg, the slag used in the present invention is a by-product produced in the blast furnace ironmaking process.
[0010] Furthermore, the phosphogypsum is hemihydrate phosphogypsum. Hemihydrate phosphogypsum (HPG) is industrial waste residue produced by phosphorus chemical enterprises in the process of wet production of phosphoric acid. Its main component is calcium sulfate dihydrate (CaSO4·2H2O). Hemihydrate calcium sulfate (CaSO4·0.5H2O) is formed after dehydration treatment. It has self-gelling properties and is highly available.
[0011] Furthermore, the CaO content in the carbide slag is ≥65.0%. The carbide slag used in the present invention is waste slag with calcium hydroxide as the main component after acetylene gas is obtained by hydrolyzing calcium carbide.
[0012] Furthermore, the specific surface area of the silica fume is ≥19.0m 2 / g, and the SiO2 content is ≥96.0%. The silica ash used in the present invention is obtained by collecting and treating the smoke escaping with the exhaust gas during the high-temperature smelting of industrial silicon and ferrosilicon in an industrial electric furnace through a capture device.
[0013] Exemplarily, the slag phosphogypsum-based solid waste cementitious material comprises, by weight percentage, 50.84% slag, 45.76% phosphogypsum, 1.40% carbide slag and 2.00% silica fume, with a water-cement ratio of 0.40.
[0014] Exemplarily, the slag phosphogypsum-based solid waste cementitious material comprises, by weight percentage, 49.81% raw materials, 44.82% phosphogypsum, 1.37% carbide slag and 4.00% silica fume, with a water-cement ratio of 0.40.
[0015] Exemplarily, the slag phosphogypsum-based solid waste cementitious material comprises, by weight percentage, 48.77% slag, 43.89% phosphogypsum, 1.34% carbide slag and 6.00% silica fume, with a water-cement ratio of 0.40.
[0016] The second technical solution of the present invention:
[0017] A method for preparing the slag phosphogypsum-based solid waste cementitious material comprises the following steps:
[0018] Weigh slag, phosphogypsum, carbide slag and silica fume according to mass percentage, mix them evenly, add water and stir to obtain slurry;
[0019] Pour the slurry into a mold, vibrate it, let it stand, and then demould it;
[0020] The demoulding specimen is subjected to standard curing to obtain the slag phosphogypsum-based solid waste cementitious material.
[0021] Further, after adding water, stirring was carried out at 140±5 r / min for 1-2 min, and then stirring was carried out at 285±10 r / min for 2-3 min.
[0022] Furthermore, curing is carried out at 20°C ± 1°C and relative humidity not less than 90%.
[0023] The third technical solution of the present invention:
[0024] Application of the slag phosphogypsum-based solid waste cementitious material in the field of construction.
[0025] The slag, phosphogypsum, carbide slag and silica fume of the present invention improve the compressive strength of the material through multiple synergistic effects when preparing the slag phosphogypsum-based solid waste cementitious material. The principle is as follows:
[0026] 1. Alkali stimulation
[0027] The main component of carbide slag is calcium hydroxide (Ca(OH)2), which has strong alkalinity and can provide an alkaline environment for the system. Under alkaline conditions, active components such as silicates and aluminates in the slag are stimulated and undergo hydration reactions to generate hydration products such as calcium silicate hydrate (CSH) gel and calcium aluminosilicate hydrate (CASH). These hydration products fill the pores of the material to form a stable skeleton structure, making the structure denser and thus improving the compressive strength.
[0028] 2. Sulfate stimulation
[0029] Phosphogypsum contains a large amount of sulfate ions (SO4 2- ), can act as a sulfate activator. Sulfate ions react with calcium ions (Ca) in slag and carbide slag. 2+ ) to generate hydration products such as ettringite (AFt). The interweaving of ettringite not only fills the pores of the material, but also forms a denser microstructure through interaction with C(A)-SH gel, further improving the strength of the material.
[0030] 3. Volcanic ash reaction
[0031] Silica fume contains highly active silicon dioxide (SiO2), which can react with calcium hydroxide (Ca(OH)2) released from carbide slag to produce more C-(A)-SH gel. This reaction not only increases the amount of hydration products, but also optimizes the pore structure of the material, making it denser.
[0032] 4. Micro-aggregate filling effect
[0033] Slag, phosphogypsum, carbide slag and silica fume have good particle gradation. In cementitious materials, these particles can be closely packed to fill each other's pores, reduce the number of macropores, and improve the microstructure of the material. This micro-aggregate filling effect can effectively improve the density of the material, thereby improving the compressive strength.
[0034] 5. Synergistic Mechanism
[0035] Chemical synergy: The alkali activation of carbide slag combined with the sulfate activation of phosphogypsum can more fully activate the activity of slag and silica fume. Slag dissolves in an alkaline environment to release calcium, aluminum and other ions, which react with sulfate ions in phosphogypsum and silica provided by silica fume to form C-(A)-SH gel and ettringite. These hydration products are intertwined to form a stable network structure.
[0036] Physical synergy: Slag and phosphogypsum have large particles that can provide skeleton support, while silica fume particles are fine and can fill the pores between large particles. The synergistic effect of this physical filling and chemical reaction makes the microstructure of the material denser.
[0037] Compared with the prior art, the present invention has the following advantages and technical effects:
[0038] (1) The present invention uses two kinds of calcium-containing solid wastes, slag and phosphogypsum, as main raw materials, uses carbide slag as an alkaline activator, and adds silica fume to further improve the performance of solid waste cementitious materials. The raw materials jointly optimize the hydration products and microstructure of the materials through the synergistic effects of alkali activation, sulfate activation, volcanic ash reaction and micro-aggregate filling. The synergistic effect reduces the porosity of the material, increases the hydration products, and makes the structure more compact, thereby significantly improving the compressive strength of the slag phosphogypsum-based solid waste cementitious materials.
[0039] (2) The slag phosphogypsum-based solid waste cementitious material of the present invention does not use chemical activators such as NaOH and Na2SiO3, but uses solid waste materials as alkaline activators, which reduces the introduction of external alkali and reduces the cost of raw materials. Compared with other solid waste cementitious materials using chemical activators, the present invention not only avoids the carbon emissions generated by the chemical activator generation process, but also has lower construction costs and safer construction.
[0040] (3) The slag phosphogypsum-based solid waste cementitious material of the present invention does not require high-temperature curing. Compared with other solid waste cementitious materials that require high-temperature curing to form strength, it can not only further reduce carbon emissions, but also shorten the construction period and improve construction efficiency.
[0041] (4) The raw material slag of the present invention is a widely used solid waste material with a relatively high price. A high dosage will increase the cost. The present invention uses phosphogypsum to replace part of the slag. On the one hand, it can alleviate the problem of large-scale accumulation of phosphogypsum, and on the other hand, it can reduce costs and increase added value.
[0042] (5) All precursor materials used in the present invention are solid wastes, and no chemical activators or high-temperature curing are required, which further reduces construction costs, carbon emissions and energy consumption. The slag phosphogypsum-based solid waste cementitious material of the present invention has high early strength, and its 28d compressive strength can reach up to 57.7MPa, which fully meets the actual engineering needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0044] Figure 1 This is a flow chart of a method for preparing a slag phosphogypsum-based solid waste cementitious material according to the present invention;
[0045] Figure 2 The compressive strength test results of the slag phosphogypsum-based solid waste cementitious materials in Examples 1-6;
[0046] Figure 3 The compressive strength test results of the slag phosphogypsum-based solid waste cementitious materials in Comparative Examples 1-7;
[0047] Figure 4 This is a scanning electron microscope (SEM) image of the slag phosphogypsum-based solid waste cementitious material prepared in Example 1. DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0052] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0053] The embodiment of the present invention proposes a slag phosphogypsum-based solid waste cementitious material. The raw materials include 45-55% slag, 40-50% phosphogypsum, 0.5-5% carbide slag and 2-10% silica fume in terms of mass percentage, and the water-cement ratio is 0.35-0.50.
[0054] In a preferred embodiment of the present invention, the slag is S95 grade or above. The slag powder is divided into three grades of S75, S95 and S105 according to the activity index. The S95 grade slag powder is a high-activity slag powder that meets the requirements of the national standard GB / T18046-2000. It is mainly made of water-quenched blast furnace slag through drying, grinding and other processes. The activity index of the S95 grade slag powder requires a 28d compressive strength ratio of ≥95% and a specific surface area of ≥350m 2 / kg, the slag used in the present invention is a by-product in the blast furnace ironmaking process. More specifically, the slag used in the embodiment of the present invention is S105 grade slag with an activity index of 106.
[0055] In a preferred embodiment of the present invention, the phosphogypsum is hemihydrate phosphogypsum. Hemihydrate phosphogypsum (HPG) is industrial waste residue produced by phosphorus chemical enterprises in the process of wet production of phosphoric acid. Its main component is calcium sulfate dihydrate (CaSO4·2H2O). Hemihydrate calcium sulfate (CaSO4·0.5H2O) is formed after dehydration treatment. It has self-gelling properties and is highly available.
[0056] In a preferred embodiment of the present invention, the CaO content in the carbide slag is ≥ 65.0%, and the carbide slag used in the present invention is waste slag with calcium hydroxide as the main component after acetylene gas is obtained by hydrolyzing carbide. More specifically, the CaO content in the carbide slag used in the embodiment of the present invention is 92.88%.
[0057] In a preferred embodiment of the present invention, the specific surface area of the silica fume is ≥19.0m 2 / g, and the SiO2 content is ≥96.0%. The silica ash used in the present invention is obtained by collecting and treating the smoke and dust emitted from the exhaust gas during the high-temperature smelting of industrial silicon and ferrosilicon in an industrial electric furnace through a special capture device. More specifically, the specific surface area of the silica ash used in the embodiment of the present invention is 19.1m 2 / g, and the SiO2 content is 96.74%.
[0058] Exemplarily, the slag phosphogypsum-based solid waste cementitious material comprises, by weight percentage, 50.84% slag, 45.76% phosphogypsum, 1.40% carbide slag and 2.00% silica fume, with a water-cement ratio of 0.40.
[0059] Exemplarily, the slag phosphogypsum-based solid waste cementitious material comprises, by weight percentage, 49.81% raw materials, 44.82% phosphogypsum, 1.37% carbide slag and 4.00% silica fume, with a water-cement ratio of 0.40.
[0060] Exemplarily, the slag phosphogypsum-based solid waste cementitious material comprises, by weight percentage, 48.77% slag, 43.89% phosphogypsum, 1.34% carbide slag and 6.00% silica fume, with a water-cement ratio of 0.40.
[0061] In a preferred embodiment of the present invention, a method for preparing the slag phosphogypsum-based solid waste cementitious material comprises the following steps:
[0062] Weigh slag, phosphogypsum, carbide slag and silica fume according to mass percentage, mix them evenly, add deionized water and stir to obtain a slurry;
[0063] Pour the slurry into a mold, vibrate it, let it stand, and then demould it;
[0064] The demoulding specimen is subjected to standard curing to obtain the slag phosphogypsum-based solid waste cementitious material.
[0065] The flow chart of the preparation method of slag phosphogypsum-based solid waste cementitious material of the present invention is shown in Figure 1 .
[0066] In a preferred embodiment of the present invention, after adding water, stirring is performed at 140±5 r / min for 1-2 min, and then stirring is performed at 285±10 r / min for 2-3 min.
[0067] In a preferred embodiment of the present invention, curing is carried out at 20°C ± 1°C and a relative humidity of not less than 90%.
[0068] The chemical compositions of slag, phosphogypsum, carbide slag and silica fume used in the embodiments of the present invention are shown in Table 1.
[0069] Table 1 Chemical composition of each raw material
[0070]
[0071] The technical solution of the present invention is further illustrated by the following embodiments.
[0072] Example 1
[0073] A slag phosphogypsum-based solid waste cementitious material, wherein the raw materials include 50.84% slag, 45.76% phosphogypsum, 1.40% carbide slag and 2.00% silica fume in terms of mass percentage, and the water-cement ratio is 0.40. The preparation method comprises the following steps:
[0074] (1) Weigh slag, phosphogypsum, carbide slag and silica fume according to the above mass percentages, and fully mix the four precursor raw materials;
[0075] (2) Add deionized water to the mixed precursor powder. First add water and then stir at 140 r / min for 2 min to fully mix the powder and water without agglomeration. Then stir at 285 r / min for 3 min to obtain a slurry with a uniform texture.
[0076] (3) Pour the stirred slurry into the mold and vibrate it on a vibration table until no obvious bubbles emerge;
[0077] (4) After standing for 1 day, the mold is demoulded. The specimen should be free from damage during the demoulding process.
[0078] (5) The demolded specimens are placed in a standard curing box at 20°C ± 1°C and a relative humidity of not less than 90% for curing. After the curing, slag phosphogypsum-based solid waste cementitious material is obtained.
[0079] Example 2
[0080] A slag phosphogypsum-based solid waste cementitious material, the raw materials of which include 49.81% by weight, 44.82% by weight of phosphogypsum, 1.37% by weight of carbide slag and 4.00% by weight of silica fume, and a water-cement ratio of 0.40;
[0081] The preparation method of slag phosphogypsum-based solid waste cementitious material is the same as that in Example 1.
[0082] Example 3
[0083] A slag phosphogypsum-based solid waste cementitious material, wherein the raw materials include 48.77% slag, 43.89% phosphogypsum, 1.34% carbide slag and 6.00% silica fume in terms of mass percentage, and the water-cement ratio is 0.40;
[0084] The preparation method of slag phosphogypsum-based solid waste cementitious material is the same as that in Example 1.
[0085] Example 4
[0086] A slag phosphogypsum-based solid waste cementitious material, wherein the raw materials include 55% slag, 40% phosphogypsum, 0.5% carbide slag and 9.5% silica fume in terms of mass percentage, with a water-cement ratio of 0.50, and the preparation method is the same as that in Example 1.
[0087] Example 5
[0088] A slag phosphogypsum-based solid waste cementitious material, wherein the raw materials include 45% slag, 50% phosphogypsum, 3% carbide slag and 2% silica fume in terms of mass percentage, with a water-cement ratio of 0.35, and the preparation method is the same as that in Example 1.
[0089] Example 6
[0090] A slag phosphogypsum-based solid waste cementitious material, wherein the raw materials include 45% slag, 40% phosphogypsum, 5% carbide slag and 10% silica fume in terms of mass percentage, with a water-cement ratio of 0.40, and the preparation method is the same as that in Example 1.
[0091] Comparative Example 1
[0092] Same as Example 1, except that the addition of phosphogypsum is omitted, and the raw materials of a solid waste cementitious material include 96.6% slag, 1.40% carbide slag and 2.00% silica fume in terms of mass percentage, and the water-cement ratio is 0.40;
[0093] The preparation method is the same as Example 1.
[0094] Comparative Example 2
[0095] Same as Example 1, except that the addition of carbide slag is omitted, and a solid waste cementitious material comprises, by weight percentage, 50.84% slag, 45.76% phosphogypsum and 3.40% silica fume, and a water-cement ratio of 0.40;
[0096] The preparation method is the same as Example 1.
[0097] Comparative Example 3
[0098] Same as Example 1, except that the addition of silica fume is omitted, and the raw materials of a solid waste cementitious material include 50.84% slag, 45.76% phosphogypsum and 3.40% carbide slag in terms of mass percentage, and the water-cement ratio is 0.40;
[0099] The preparation method is the same as Example 1.
[0100] Comparative Example 4
[0101] Same as Example 1, except that, a slag phosphogypsum-based solid waste cementitious material, in terms of mass percentage, comprises 65% slag, 20% phosphogypsum, 10% carbide slag and 5% silica fume, and a water-cement ratio of 0.40;
[0102] The preparation method is the same as Example 1.
[0103] Comparative Example 5
[0104] The same as Example 1, except that the water-cement ratio of the slag phosphogypsum-based solid waste cementitious material is 0.60.
[0105] Comparative Example 6
[0106] The same as Example 1, except that the water-cement ratio of the slag phosphogypsum-based solid waste cementitious material is 0.20.
[0107] Comparative Example 7
[0108] Same as Example 1, except that the mass of carbide slag is replaced by calcium hydroxide.
[0109] The raw material composition of the slag phosphogypsum-based solid waste cementitious material precursor material in the embodiments and comparative examples is shown in Table 2.
[0110] Table 2 Composition of slag phosphogypsum-based solid waste cementitious material precursors in the examples and comparative examples (mass percentage, %)
[0111]
[0112] Performance Testing
[0113] Referring to GB / T17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", the compressive strength of the slag phosphogypsum-based solid waste cementitious materials in Examples 1-6 and Comparative Examples 1-7 was tested at 3d, 7d, 14d and 28d respectively. The compressive strength test results of the slag phosphogypsum-based solid waste cementitious materials in Examples 1-6 are shown in Figure 2 The compressive strength test results of slag phosphogypsum-based solid waste cementitious materials in Comparative Examples 1-7 are shown in Figure 3 It can be seen that the slag phosphogypsum-based solid waste cementitious materials have excellent mechanical properties. This is because several raw materials can undergo hydration reactions under alkaline conditions to generate hydration products such as calcium silicate hydrate (CSH), calcium aluminate hydrate (CAH), calcium aluminosilicate hydrate (CASH) and ettringite, which improves the strength of the material and the 28d compressive strength reaches 57.7MPa.
[0114] Compared with Example 1, the addition of phosphogypsum was omitted in Comparative Example 1, resulting in a lack of sulfate ions necessary for the formation of ettringite in the system, and because the slag lost the sulfate activation effect provided by the phosphogypsum, the strength of the solidified slurry was significantly reduced;
[0115] Compared with Example 1, Comparative Example 2 omitted the addition of carbide slag, resulting in the system being unable to form an alkaline environment, unable to destroy the structure of the slag particles to release the active ingredients, and unable to carry out the hydration reaction. The self-activation efficiency of the slag itself is limited, thereby significantly reducing the strength of the solidified slurry.
[0116] Compared with Example 1, Comparative Example 3 omits the addition of silica fume, resulting in the inability to consume excess hydroxide ions in the later system, deterioration of the hydration product gel, and the continued hydration process will also cause the deterioration of the calcium hydroxide crystal structure. In addition, the micro-filling effect and nucleation effect of silica fume will be lost. All of these will cause the compressive strength of the cured slurry to decrease in the later stage;
[0117] Compared with Example 1, Comparative Example 4 changes the dosage ratio of each raw material, resulting in a weakened synergistic effect between the precursor materials. For example, when the amount of carbide slag is too much, calcium hydroxide crystals will precipitate, forming a large number of pores and stress concentration areas inside the solidified slurry, which will have an adverse effect on the strength; when the amount of silica fume is too much, the alkalinity of the system will be reduced, which will affect the dissolution of the precursor material and the hydration reaction, thereby reducing the strength;
[0118] Compared with Example 1, Comparative Examples 5 and 6 changed the water-cement ratio. First, too low a water-cement ratio will cause the slurry to lose workability and fail to undergo effective hydration. Second, too high a water-cement ratio will result in too high a moisture content in the slurry, and the pores formed after the internal moisture evaporates will result in reduced compressive strength.
[0119] Compared with Example 1, Comparative Example 7 uses a traditional calcium hydroxide alkaline activator to replace carbide slag, resulting in increased costs and carbon emissions. In addition, the use of a strong alkaline chemical activator will have safety risks and will cause the slurry to have problems such as reduced durability, poor volume stability, and easy carbonization.
[0120] The scanning electron microscope (SEM) image of the slag phosphogypsum-based solid waste cementitious material prepared in Example 1 of the present invention is shown in Figure 4,It can be seen that at this time, the ettringite and C-(A)-SH gel are interconnected to form a whole, and the number of pores and microcracks inside the solidified slurry is small.
[0121] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A slag phosphogypsum-based solid waste cementitious material, characterized in that: Calculated by mass percentage, the raw materials include 45-55% slag, 40-50% phosphogypsum, 0.5-5% carbide slag and 2-10% silica fume, and the water-cement ratio is 0.35-0.
50.
2. The slag phosphogypsum-based solid waste cementitious material according to claim 1, characterized in that: The slag is S95 grade or above; the phosphogypsum is hemihydrate phosphogypsum; the CaO mass content in the carbide slag is ≥65.0%; the specific surface area of the silica fume is ≥19.0m 2 / g, and the SiO2 mass content is ≥96.0%.
3. The slag phosphogypsum-based solid waste cementitious material according to claim 1, characterized in that: In terms of mass percentage, the raw materials include 50.84% slag, 45.76% phosphogypsum, 1.40% carbide slag and 2% silica fume, and the water-cement ratio is 0.
40.
4. The slag phosphogypsum-based solid waste cementitious material according to claim 1, characterized in that: Calculated by mass percentage, the raw materials include 49.81% slag, 44.82% phosphogypsum, 1.37% carbide slag and 4% silica fume, and the water-cement ratio is 0.
40.
5. The slag phosphogypsum-based solid waste cementitious material according to claim 1, characterized in that: In terms of mass percentage, the raw materials include 48.77% slag, 43.89% phosphogypsum, 1.34% carbide slag and 6% silica fume, and the water-cement ratio is 0.
40.
6. A method for preparing the slag phosphogypsum-based solid waste cementitious material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Weigh slag, phosphogypsum, carbide slag and silica fume according to mass percentage, mix them evenly, add water and stir to obtain slurry; Pour the slurry into a mold, vibrate it, let it stand, and then demould it; The demoulding specimen is subjected to standard curing to obtain the slag phosphogypsum-based solid waste cementitious material.
7. The method for preparing slag phosphogypsum-based solid waste cementitious material according to claim 6, characterized in that: After adding water, stir at 140±5 r / min for 1-2 min, and then stir at 285±10 r / min for 2-3 min.
8. The method for preparing slag phosphogypsum-based solid waste cementitious material according to claim 6, characterized in that: Maintain at 20℃±1℃ and relative humidity not less than 90%.
9. Use of the slag phosphogypsum-based solid waste cementitious material according to any one of claims 1 to 5 in the field of construction.
Citation Information
Patent Citations
All-solid waste cementing material as well as preparation method and application thereof
CN113149477A
Environmental-friendly clinker-free cement and preparation method thereof
CN101525217A
Phosphogypsum-based cementing material and preparation method thereof
CN116102271A
All-solid waste cementing material containing lithium slag and preparation method of all-solid waste cementing material
CN118344033A
Micro-granulose particulates
US20030089281A1
Cited By
Ardealite stabilizer for ardealite road and laying method of ardealite road
CN121470906A
Phosphogypsum stabilizer for phosphogypsum roads and method for laying phosphogypsum roads
CN121470906B
Green and harmless solid-waste-based micro-expansive impermeable full-recycled concrete and preparation method thereof
CN121673013A
Phosphogypsum-based fine aggregate as well as preparation method and application thereof
CN121850420A
Gypsum slag-based super-retarding material and preparation method thereof
CN122187404A